Secondary battery

By employing silicon particles with a clathrate structure and controlled particle size, the durability of silicon-based batteries is enhanced by stabilizing the structure and reducing structural collapse during charging and discharging.

JP7615966B2Active Publication Date: 2025-01-17TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021136589
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-24
Publication Date
2025-01-17
Estimated Expiration
2041-08-24

AI Technical Summary

Technical Problem

Batteries using silicon-based negative electrode active materials face durability issues due to the collapse of the clathrate structure during charging and discharging, particularly when the particle size is too large.

Method used

The use of silicon particles with a clathrate structure and an average particle diameter of 0.7 μm to 8.9 μm, along with a specific ratio of Raman spectroscopy peak intensities, to stabilize the structure and enhance durability.

Benefits of technology

The secondary battery exhibits improved durability by minimizing the expansion and contraction of silicon particles, maintaining the clathrate structure and enhancing the battery's longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615966000002
    Figure 0007615966000002
  • Figure 0007615966000001
    Figure 0007615966000001
Patent Text Reader

Abstract

To improve the durability of a secondary battery using a silicon negative electrode active material.SOLUTION: A secondary battery 100 has a negative electrode 10, an electrolyte, and a positive electrode 30. The negative electrode 10 includes Si particles as a negative electrode active material. The Si particles have a clathrate structure. An average particle size of the Si particles is 0.7-8.9 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application discloses a secondary battery using a silicon-based negative electrode active material. [Background technology]

[0002] Batteries using silicon-based negative electrode active materials are known. For example, Patent Document 1 discloses a lithium ion secondary battery using silicon oxide as the negative electrode active material. Patent Document 2 discloses a lithium ion secondary battery using silicon clathrate II as the negative electrode active material. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-113547 A [Patent Document 2] Patent Publication No. 2021-034279 Summary of the Invention [Problem to be solved by the invention]

[0004] There is room for improvement in the durability of batteries using silicon-based negative electrode active materials. [Means for solving the problem]

[0005] As one of the means for solving the above problems, the present application provides: A secondary battery having a negative electrode, an electrolyte, and a positive electrode, The negative electrode contains Si particles as a negative electrode active material, The Si particles have a clathrate structure, The Si particles have an average particle size of 0.7 μm or more and 8.9 μm or less. secondary battery Disclose.

[0006] In the secondary battery of the present disclosure, the clathrate structure has a surface area of ​​325±10 cm measured by Raman spectroscopy. -1 Maximum peak intensity at I 325 and 205±10cm -1 Maximum peak intensity at I 205 Comparison with I 325 / I 205 may be within the range of 1.03 to 1.21.

[0007] In the secondary battery of the present disclosure, the Si particles may have an average particle size of 2.8 μm or more and 8.9 μm or less. Effect of the Invention

[0008] The secondary battery of the present disclosure has excellent durability. [Brief description of the drawings]

[0009] [Figure 1] 1 shows a schematic configuration of a secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The secondary battery of the present disclosure has a negative electrode, an electrolyte, and a positive electrode. Here, the negative electrode contains Si particles as a negative electrode active material, the Si particles have a clathrate structure, and the Si particles have an average particle size of 0.7 μm or more and 8.9 μm or less. FIG. 1 shows a schematic configuration of a secondary battery 100 according to an embodiment. As shown in FIG. 1, the secondary battery 100 has a negative electrode 10, a separator 20, and a positive electrode 30. Each of the negative electrode 10, the separator 20, and the positive electrode 30 may be in contact with or impregnated with an electrolyte (not shown).

[0011] 1.Negative electrode The negative electrode 10 contains Si particles as a negative electrode active material. As shown in Fig. 1, the negative electrode 10 may include a negative electrode active material layer 11 and a negative electrode current collector 12. In this case, the negative electrode active material layer 11 may contain Si particles as a negative electrode active material.

[0012] 1.1 Negative electrode active material layer The negative electrode active material layer 11 contains Si particles as a negative electrode active material, and may further contain a conductive assistant, a binder, and the like. The content of each component in the negative electrode active material layer 11 is not particularly limited, and may be appropriately determined according to the performance of the target battery. For example, the content of the negative electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, assuming that the entire negative electrode active material layer 11 (total solid content) is 100 mass%. The thickness of the negative electrode active material layer 11 is also not particularly limited, and may be, for example, 1 μm or more, 10 μm or more, or 30 μm or more, and may be 1 mm or less, 500 μm or less, or 100 μm or less.

[0013] 1.1.1 Negative electrode active material The Si particles as the negative electrode active material have a clathrate structure. When the Si particles have a clathrate structure, the expansion and contraction of the Si particles accompanying the charging and discharging of the battery becomes relatively small, and the durability of the battery is easily improved. Whether or not the Si particles have a clathrate structure can be easily determined from Raman spectroscopy. In the present application, the 325±10 cm -1 Maximum peak intensity at I 325 and 205±10cm -1 Maximum peak intensity at I 205 Comparison with I 325 / I 205 is in the range of 1.03 to 1.21, the Si particles are considered to have a clathrate structure.

[0014] The Si particles as the negative electrode active material have an average particle diameter of 0.7 μm or more and 8.9 μm or less. If the average particle diameter of the Si particles is too large, it becomes difficult to maintain the clathrate structure after charging and discharging the battery. This is presumed to be due to the following mechanism. That is, in a secondary battery, the reaction proceeds rapidly on the Si surface in contact with the electrolyte. If the Si particles are too large, the specific surface area becomes small, the concentration of the reaction increases, and the clathrate structure is likely to collapse. According to the knowledge of the present inventor, such problems are easily avoided by setting the average particle diameter of the Si particles to 8.9 μm or less. The lower limit of the average particle diameter of the Si particles is 0.7 μm or more, and may be 2.8 μm or more. The average particle diameter of the Si particles is the particle diameter (median diameter) at 50% of the cumulative value in the volume-based particle size distribution obtained by the laser diffraction and scattering method.

[0015] In addition to the above-mentioned Si particles, the negative electrode active material layer 11 may contain other negative electrode active materials as the negative electrode active material. For example, the negative electrode active material layer 11 may contain at least one selected from silicon-based active materials such as Si other than clathrate silicon, Si alloys, and silicon oxide, carbon-based active materials such as graphite and hard carbon, various oxide-based active materials such as lithium titanate, metallic lithium, lithium alloys, and the like as the other negative electrode active materials.

[0016] 1.1.2 Conductive additives Examples of the conductive assistant include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.

[0017] 1.1.3 Binders Examples of the binder include polyimide (PI)-based binders, butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, and polytetrafluoroethylene (PTFE)-based binders. In particular, when the negative electrode active material layer 11 contains polyimide as a binder, the expansion and contraction of the Si particles is more easily suppressed. The polyimide may be obtained by heating a polyamic acid to cause an imidization reaction (dehydration and cyclization). The polyamic acid may be aromatic or aliphatic, but is preferably one having an aromatic ring from the viewpoint of being a high-strength binder when it becomes a polyimide. Only one type of binder may be used alone, or two or more types may be used in combination.

[0018] 1.2 Negative electrode current collector The negative electrode current collector 12 may be any of those generally used as negative electrode current collectors for secondary batteries. The negative electrode current collector 12 may be in the form of a foil, a plate, a mesh, a punched metal, or a foam. The negative electrode current collector 12 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, metal foil is excellent in terms of ease of handling. The negative electrode current collector 12 may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode current collector 12 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector 12 may contain at least one metal selected from Cu, Ni, and stainless steel. The negative electrode current collector 12 may have some kind of coating layer on its surface for the purpose of adjusting resistance, etc. The negative electrode current collector 12 may be a metal foil or a substrate plated or vapor-deposited with the above metal. When the negative electrode current collector 12 is made of a plurality of metal foils, some layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 12 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0019] 2. Separator As shown in FIG. 1, a separator 20 may be disposed between the negative electrode 10 and the positive electrode 30. The separator 20 has a function of preventing contact between the negative electrode 10 and the positive electrode 30 and holding an electrolyte solution described later to form an electrolyte layer. The separator may be any separator that is commonly used in secondary batteries, and may be made of resin such as polyethylene (PE), polypropylene (PP), polyester, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer structure separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be made of a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric. The thickness of the separator is not particularly limited, and may be, for example, 5 μm or more and 1 mm or less.

[0020] 3.Positive electrode 1, the positive electrode 30 may include a positive electrode active material layer 31 and a positive electrode current collector 32. In this case, the positive electrode active material layer 31 may include a positive electrode active material.

[0021] 3.1 Cathode active material layer The positive electrode active material layer 31 includes a positive electrode active material, and may further include a conductive assistant, a binder, and the like. The content of each component in the positive electrode active material layer 31 is not particularly limited, and may be appropriately determined according to the performance of the target battery. For example, the content of the positive electrode active material may be 50 mass% or more, 60 mass% or more, or 70 mass% or more, and may be 100 mass% or less, or 90 mass% or less, with the entire positive electrode active material layer 31 (total solid content) being 100 mass%. The thickness of the positive electrode active material layer 31 is also not particularly limited, and may be, for example, 1 μm or more, 10 μm or more, or 30 μm or more, and may be 1 mm or less, 500 μm or less, or 100 μm or less.

[0022] 3.1.1 Cathode active material The positive electrode active material may be any known positive electrode active material for secondary batteries. Among known active materials, a material that exhibits a potential (charge / discharge potential) at which a specific ion is absorbed and released that is higher than the above-mentioned Si-based negative electrode active material may be used as the positive electrode active material. For example, when a lithium ion battery is constructed, lithium cobalt oxide, lithium nickel oxide, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Various lithium-containing composite oxides such as lithium manganate, lithium spinel-based lithium compounds, etc. may be used. Only one type of positive electrode active material may be used alone, or two or more types may be used in combination. The positive electrode active material may be, for example, particulate, and the size is not particularly limited. The particles of the positive electrode active material may be solid particles or hollow particles. The particles of the positive electrode active material may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles. The average particle size of the particles of the positive electrode active material may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less.

[0023] 3.1.2 Conductive additives and binders The conductive assistant and the binder may be appropriately selected from those exemplified as those that can be contained in the negative electrode active material layer 11. The conductive assistant and the binder may each be used alone or in combination of two or more kinds.

[0024] 3.2 Positive electrode current collector The positive electrode collector 32 may be any of those generally used as a positive electrode collector for a secondary battery. The positive electrode collector 32 may be in the form of a foil, a plate, a mesh, a punched metal, or a foam. The positive electrode collector 32 may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector 32 may be made of a plurality of foils. Examples of metals constituting the positive electrode collector 32 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel. In particular, the positive electrode collector 32 may contain Al from the viewpoint of ensuring oxidation resistance. The positive electrode collector 32 may have some kind of coating layer on its surface for the purpose of adjusting resistance. The positive electrode collector 32 may be a metal foil or a base material on which the above metal is plated or vapor-deposited. In addition, when the positive electrode current collector 32 is made of multiple metal foils, some layer may be present between the multiple metal foils. The thickness of the positive electrode current collector 32 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0025] 4. Electrolyte The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be either an aqueous electrolyte or a non-aqueous electrolyte, but non-aqueous electrolytes have particularly high performance. The composition of the electrolyte may be the same as that of electrolytes for secondary batteries. For example, an electrolyte in which a lithium salt is dissolved at a predetermined concentration in a carbonate-based solvent may be used. Examples of carbonate-based solvents include fluoroethylene carbonate (FEC), ethylene carbonate (EC), and dimethyl carbonate (DMC). Examples of lithium salts include LiPF 6 etc.

[0026] 5. Other configurations The secondary battery 100 may be one in which each of the above-mentioned components is housed inside an exterior body. Any known exterior body for a battery can be adopted as the exterior body. In addition, a plurality of secondary batteries 100 may be arbitrarily electrically connected and arbitrarily stacked to form an assembled battery. In this case, the assembled battery may be housed inside a known battery case. The secondary battery 100 may also have other obvious components such as necessary terminals. Examples of the shape of the secondary battery 100 include a coin type, a laminate type, a cylindrical type, and a square type. As described above, the secondary battery 100 may be a lithium ion secondary battery or other secondary batteries, but a higher effect can be expected when it is a lithium ion secondary battery.

[0027] The secondary battery 100 can be manufactured by applying a known method. For example, it can be manufactured as follows. However, the method for manufacturing the secondary battery 100 is not limited to the following method. (1) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents may be used, and may be N-methylpyrrolidone (NMP). The negative electrode layer slurry is applied to the surface of a negative electrode current collector using a doctor blade or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector, thereby forming a negative electrode. (2) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used, and N-methylpyrrolidone (NMP) can also be used. The positive electrode layer slurry is applied to the surface of a positive electrode current collector using a doctor blade or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector, which serves as a positive electrode. (3) A separator is sandwiched between the negative electrode and the positive electrode to obtain a laminate having a negative electrode current collector, a negative electrode active material layer, a separator, a positive electrode active material layer, and a positive electrode current collector in this order. Other members such as terminals are attached to the laminate as necessary. (4) The laminate is housed in a battery case, and the battery case is filled with an electrolyte, and the laminate and the electrolyte are sealed in the battery case so that the laminate is immersed in the electrolyte, to produce a secondary battery. Note that the electrolyte may be impregnated into the negative electrode active material layer, the separator, and the positive electrode active material layer in the above step (3). EXAMPLES

[0028] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.

[0029] 1. Preparation of silicon negative electrode active material As the silicon negative electrode active material, crystalline silicon and clathrate silicon were each prepared.

[0030] 1.1 Preparation of crystalline silicon Silicon particles (Kojundo Kagaku, 5 μm) were milled using a planetary ball mill (Fritsch Classic Line) to obtain crystalline silicon powders with various average particle sizes. The crystalline silicon did not have a clathrate structure.

[0031] 1.2 Preparation of silicon clathrate Si particles and Na particles were mixed in a molar ratio of 1:1 and heated at 700°C to synthesize NaSi. The mixture was then heated at 340°C to remove Na. The mixture was then heated at 430°C to further remove Na, after which it was pulverized using a planetary ball mill to obtain powders with various average particle sizes. All of the obtained powders had a clathrate structure (clathrate silicon).

[0032] 2. Preparation of Positive Electrode In a PP container, NMP as a solvent, a 5 wt% butyl butyrate solution of a PVDF-based binder, and LiNi as a positive electrode active material were placed. 1 / 3 Co 1 / 3 Mn 1 / 3 O 2(average particle diameter 6 μm) and VGCF as a conductive additive were added, and the mixture was stirred for 10 minutes with a mixer (ARE-310, manufactured by Thinky Corporation) to obtain a positive electrode slurry. The positive electrode slurry was applied to an Al foil (manufactured by Showa Denko K.K.) by the blade method using an applicator. The applied electrode was dried on a hot plate at 80°C for 60 minutes.

[0033] 3. Preparation of the Negative Electrode NMP as a solvent, polyamic acid (U Varnish A, Ube Industries) as a binder to become polyimide, silicon active material as a negative electrode active material, and VGCF and KB as conductive assistants were added to a PP container, and stirred for 10 minutes with a mixer (ARE-310, Thinky Corporation) to obtain a negative electrode slurry. The mixture was applied to Cu foil (Furukawa Electric Co., Ltd.) by the blade method using an applicator. The coated electrode was dried on a hot plate at 80°C for 60 minutes.

[0034] 4. Battery Preparation The prepared positive electrode was punched out to a diameter of 14 mm, while the negative electrode was punched out to a diameter of 16 mm, and then set in a roll press machine and pressed at 20 kN / cm. The negative electrode was then baked in an Ar atmosphere at 350°C for 2 hours to cause an imidization reaction of the polyamic acid. Each electrode was moved to a glove box, and an electrolyte (1.2M LiPF 6 Solution. 1 ml of the solvent FEC:EC:EMC:DMC = 1:2:4:3 vol%) was dropped, a separator (made of PP) was laminated, 1 ml of the electrolyte was dropped again, and then the positive electrode was laminated to produce a coin cell using an automatic coin cell crimping machine (manufactured by Hosensha).

[0035] 4.1 Comparative Example 1 In the coin cell, crystalline silicon without a clathrate structure was used as the silicon negative electrode active material. The average particle size of the silicon negative electrode active material was 2.6 μm.

[0036] 4.2 Comparative Example 2 In the coin cell, crystalline silicon without a clathrate structure was used as the silicon negative electrode active material. The average particle size of the silicon negative electrode active material was 0.7 μm.

[0037] 4.3 Comparative Example 3 In the coin cell, clathrate silicon was used as the silicon negative electrode active material, and the average particle size of the silicon negative electrode active material was 25.0 μm.

[0038] 4.4 Comparative Example 4 In the coin cell, clathrate silicon was used as the silicon negative electrode active material, and the average particle size of the silicon negative electrode active material was 11.9 μm.

[0039] 4.5 Example 1 In the coin cell, clathrate silicon was used as the silicon negative electrode active material, and the average particle size of the silicon negative electrode active material was 2.8 μm.

[0040] 4.6 Example 2 In the coin cell, clathrate silicon was used as the silicon negative electrode active material, and the average particle size of the silicon negative electrode active material was 4.6 μm.

[0041] 4.7 Example 3 In the coin cell, clathrate silicon was used as the silicon negative electrode active material, and the average particle size of the silicon negative electrode active material was 0.7 μm.

[0042] 4.8 Example 4 In the coin cell, clathrate silicon was used as the silicon negative electrode active material, and the average particle size of the silicon negative electrode active material was 8.9 μm.

[0043] 5. Charge / discharge cycle test The produced coin cell was charged at a constant current of 0.2 mA to 4.2 V, and then discharged at 0.2 mA to 2.5 V, with the battery capacity at this time taken as the initial capacity. The charge-discharge test was repeated 50 times, in which the battery was charged at a constant current of 2 mA to 4.2 V, and then discharged at a constant current of 2 mA. Thereafter, the battery capacity was measured when the battery was charged at a constant current of 0.2 mA to 4.2 V, and then discharged at 0.2 mA to 2.5 V, and the ratio to the initial capacity was calculated to confirm the durability performance after 50 cycles. The durability performance of Comparative Example 1 was taken as the standard (100%), and the durability performance of Comparative Examples 2 to 4 and Examples 1 to 4 was evaluated relative to each other.

[0044] In addition, the negative electrode was taken out after the first charge and discharge and measured by Raman spectroscopy (wavelength 532 nm). The obtained Raman spectrum was analyzed and found to have a peak intensity of 325±10 cm -1 Maximum peak intensity at I 325 and 205±10cm -1 Maximum peak intensity at I 205 Comparison with I 325 / I 205 The ratio I was calculated. 325 / I 205 When the ratio is within the range of 1.03 to 1.21, it can be said that the Si particles have a clathrate structure.

[0045] 6. Evaluation Results The evaluation results are shown in Table 1 below.

[0046] [Table 1]

[0047] The results shown in Table 1 reveal the following. First, a comparison of Comparative Examples 1 and 2 with Examples 1 to 4 reveals that the durability of a secondary battery is higher when clathrate silicon is used as the negative electrode active material than when crystalline silicon without a clathrate structure is used. This is believed to be due to the fact that clathrate silicon expands and contracts less during charging and discharging the battery than crystalline silicon.

[0048] In addition, from the comparison of Comparative Examples 3 and 4 with Examples 1 to 4, it can be seen that even if clathrate silicon is used as the negative electrode active material, if the particle size is too large, the durability of the secondary battery is reduced. This is presumed to be due to the following mechanism. That is, in a secondary battery, the reaction proceeds rapidly on the Si surface in contact with the electrolyte. It is considered that if the Si particles are too large, the specific surface area becomes small, the reaction concentration increases, and the clathrate structure is easily broken. That is, in Comparative Examples 3 and 4, even if the clathrate structure is maintained after the initial charge and discharge, it is considered that the clathrate structure is gradually broken by repeating charge and discharge, and the capacity of the negative electrode is ultimately greatly reduced.

[0049] In the above examples, examples using a specific positive electrode and electrolyte solution were shown, but the technology of the present disclosure does not particularly limit the type of positive electrode and electrolyte solution. In addition, in the above examples, a form using a specific current collector, binder, and conductive assistant was shown in the negative electrode, but the technology of the present disclosure does not particularly limit the configuration other than the negative electrode active material in the negative electrode. From the above estimated mechanism, it is considered that the durability of the secondary battery is improved by using a specific negative electrode active material in any configuration.

[0050] From the above results, it can be said that the secondary battery having the following configurations (1) to (4) has excellent durability. (1) It is a so-called electrolyte battery having a negative electrode, an electrolyte, and a positive electrode. (2) The negative electrode contains Si particles as a negative electrode active material. (3) The Si particles have a clathrate structure. (4) The silicon particles have an average particle size of 0.7 μm or more and 8.9 μm or less. [Explanation of symbols]

[0051] 10 negative electrode 11 Negative electrode active material layer 12 Negative electrode current collector 20 Separator 30 positive electrode 31 Positive electrode active material layer 32 Positive electrode current collector 100 Secondary battery

Claims

1. A secondary battery having a negative electrode, an electrolyte, and a positive electrode, The negative electrode contains Si particles as a negative electrode active material, The Si particles have a clathrate structure, The Si particles have an average particle size of 2.8 μm or more and 8.9 μm or less. Secondary battery.

2. The clathrate structure has a wavelength of 325±10 cm as measured by Raman spectroscopy. -1 Maximum peak intensity I 325 and 205±10cm -1 Maximum peak intensity I 205 Comparison with I 325 / I 205 is in the range of 1.03 to 1.21, The secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Manufacturing method of active material, active material and battery

    JP2020064716A

  • Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery and lithium ion secondary battery

    JP2020113547A

  • Negative electrode active material including silicon clathrate ii

    JP2021034279A

  • Type ii clathrates for rechargeable battery anodes

    US20150380724A1